Tarantino’s Inglourious Basterds: a blueprint for dubbing translators? - Mingant, Nolwenn (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2010)
Released in 2009, Quentin Tarantino’s Inglourious Basterds is representative of a recent trend of multilingual films in Hollywood. The inclusion of one or several languages other than English can be problematic for dubbing translators when the films is exported. The comparison between the original version of Inglourious Basterds and its French dubbed version offered in this article brings to light a number of translation issues. The idea of the codified relationship with the audience leads us to explore notions of conventions, contrivances, and suspension of disbelief, whether in the native language or original subtitling included in the American version. Dubbing is not only translating, it raises the issue of the texture of the original voices, especially in a film preoccupied with accents. Finding French voices with an equivalent texture but which are also plausible for the audience is a challenge that the dubbing team must meet. Finally, the vital importance of languages in the narrative and thematic construction of Tarantino’s film result in the inevitable loss due to the dubbing process. This article is not an attack on the dubbing process, but an attempt to interrogate its complexity and determine its role.